Pandémie à SARS-CoV-2 : éthique et intégrité oubliées devant la précipitation pour publier - Maisonneuve, Hervé (La Presse Médicale Formation, 2020)
The publishers, owners of the journals along with the learned societies, have made COVID-19 articles freely available, with a dedicated space. Prestigious medical journals received up to 100 manuscripts per day, publishing less than 2–3%, and peer review standards were not always followed. Journals have created new sections to lower publication standards, attract authors, or increase citation numbers; manipulations of publications have been observed. Predatory journals, including some created during the pandemic, took advantage of the pandemic to attract articles. Doctors have adopted the preprints system, after being reserved about its usefulness. Scientific journals are no longer the first to publish research results.